Dataset of Environmental factors regulating gaping activity of the bivalve Arctica islandica in Northern Norway - Ballesta-Artero, Irene (NIOZ Royal Netherlands Institute for Sea Research, 2017)
Average gaping activity per month of 16 specimens of Arctica islandica + enviromental factors (Temperature, Salinity,Light,Chl-a, Turbidity,and Sea Level) of Ingøya, northern Norway